2002
DOI: 10.1016/s0002-9440(10)64483-5
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin-L, a Key Molecule in the Pathogenesis of Drug-Induced and I-Cell Disease-Mediated Gingival Overgrowth

Abstract: Drug-induced gingival overgrowth, the chronic side effect of calcium antagonists, is frequently seen due to the increase in patients with hypertension, although the etiology of the disease is largely unknown. I-cell disease, which accompanies gingival overgrowth, is characterized by a deficiency in UDP-N-acetyl-glucosamine and is classified as one of the lysosomal storage diseases. Here, we hypothesized that a common mechanism may underlie the etiology of gingival overgrowth seen in patients treated with calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 24 publications
2
33
0
Order By: Relevance
“…In addition, we have demonstrated that longterm exposure to CsA impairs both cathepsin B and L activity in HGFs (Yamaguchi et al 2004). Importantly, we have observed that mice deficient in the cathepsin L gene manifest enlarged gingiva (Nishimura et al 2002). These observations support the notion that the down-regulation of cathepsin B or L plays an crucial role in the development of gingival overgrowth.…”
Section: Introductionsupporting
confidence: 77%
“…In addition, we have demonstrated that longterm exposure to CsA impairs both cathepsin B and L activity in HGFs (Yamaguchi et al 2004). Importantly, we have observed that mice deficient in the cathepsin L gene manifest enlarged gingiva (Nishimura et al 2002). These observations support the notion that the down-regulation of cathepsin B or L plays an crucial role in the development of gingival overgrowth.…”
Section: Introductionsupporting
confidence: 77%
“…Consistent results were found in cathepsin-L-deficient mice that exhibited enlarged gingival epithelial and connective tissues (Nishimura et al, 2002). The authors note that humans lacking lysozomal enzymes as a result of the rare genetic disease I-cell disease or mucolipidosis also have gingival overgrowth (Nishimura et al, 2002). Thus, inhibition of phagocytosis or of lysozomal enzymes appears likely to be a mechanism that could contribute to gingival overgrowth.…”
Section: Gingival Overgrowth and Diminished Tissue Resorptionmentioning
confidence: 59%
“…Cyclosporin may also inhibit phagocytosis of type I collagen in vitro and in vivo (Kataoka et al, 2000;Arora et al, 2001). Consistent results were found in cathepsin-L-deficient mice that exhibited enlarged gingival epithelial and connective tissues (Nishimura et al, 2002). The authors note that humans lacking lysozomal enzymes as a result of the rare genetic disease I-cell disease or mucolipidosis also have gingival overgrowth (Nishimura et al, 2002).…”
Section: Gingival Overgrowth and Diminished Tissue Resorptionmentioning
confidence: 75%
“…Major insights into the function of cathepsin L in the skin result from analysis of mice with targeted inactivation of the CTSL gene (ctsl -/-mice) and from the spontaneous mouse mutations nackt (ctsl nkt /ctsl nkt ) and furless (fs -/fs -) for which the cathepsin L gene has been identified as the target (Benavides et al, 2002;Roth et al, 2000). Cathepsin L-deficient (ctsl -/-) mice develop periodic hair loss, gingival acanthosis and epidermal hyperplasia with hyperkeratosis (Nishimura et al, 2002;Tobin et al, 2002). Impaired differentiation of hair follicle epithelial cells and hyperproliferation of basal epidermal keratinocytes are the primary characteristics of the ctsl -/-phenotype.…”
mentioning
confidence: 99%